Vantagem comparativa e especializaç\~ao no comércio internacional: Brasil e países selecionados - José Eustáquio Ribeiro Vieira Filho; Zenaide Rodrigues Ferreira (Instituto de Pesquisa Econômica Aplicada (IPEA), 2024)
– This study analyzes the specialization of a group of countries (Argentina, Bolivia, Brazil, Colombia, Ecuador, United States, Guatemala, Mexico, Peru and Uruguay) in international trade from 2000 to 2021. For the comparison, it was calculated indicators of revealed comparative advantage (VCR), contribution to the trade balance (CSC) and coverage rate. The results showed that there is leadership in different indicators for Argentina, Brazil and the United States. There are individual cases, in other countries, of products that stand out in the assessment as a whole. During the period evaluated, Brazil gained market share, becoming a more competitive economy over time in agribusiness.
Keywords: Q17; O13; O24; O5; 330; agribusiness; growth; exports; subsidies